A rapidly photo-activatable light-up fluorescent nucleoside and its application in DNA base variation sensing. Issue 55 (17th June 2016) - He, Zhiyong; Chen, Yuqi; Wang, Yafen; Wang, Jiaqi; Mo, Jing; Fu, Boshi; Wang, Zijing; Du, Yuhao; Zhou, Xiang
Abstract : A new DNA building block (d Tet U) bearing a tetrazole and allyloxy group at N -phenyl ring linked through an aminopropynyl linker to the 5-position of 2′-deoxyuridine was synthesized. Abstract : A new DNA building block (d Tet U) bearing a tetrazole and allyloxy group at N -phenyl ring linked through an aminopropynyl linker to the 5-position of 2′-deoxyuridine was synthesized. The modified DNA can be lit up via a photoinduced intramolecular tetrazole–alkene cycloaddition reaction, but quenched when the fully-matched double strand is formed. This conspicuous difference in fluorescence could open a door for DNA single nucleotide polymorphism (SNP) typing.